2015
DOI: 10.1038/srep11371
|View full text |Cite
|
Sign up to set email alerts
|

Surface modification of microparticles causes differential uptake responses in normal and tumoral human breast epithelial cells

Abstract: The use of micro- and nanodevices as multifunctional systems for biomedical applications has experienced an exponential growth during the past decades. Although a large number of studies have focused on the design and fabrication of new micro- and nanosystems capable of developing multiple functions, a deeper understanding of their interaction with cells is required. In the present study, we evaluated the effect of different microparticle surfaces on their interaction with normal and tumoral human breast epith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
67
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(70 citation statements)
references
References 48 publications
3
67
0
Order By: Relevance
“…Non-CSFE-labeled NDMPs (Figure 5c,d, top) and CSFE-labeled NDMPs (Figure 5c,d, bottom) were co-incubated non-trypan blue-labeled (Figure 5c) and trypan-blue labeled (Figure 5d) peritoneal myeloid cells from naive mice for 1 hour. Treatment with CSFE-labeled NDMPs of quenched, trypan blue-labeled myeloid cells demonstrates persistent CSFE uptake, indicating NDMP endocytosis (46). Taken together, these data demonstrate that the majority of NDMPs express PS, which likely serves as an uptake signal to surrounding phagocytes, specifically F4/80 macrophages.…”
Section: Resultsmentioning
confidence: 99%
“…Non-CSFE-labeled NDMPs (Figure 5c,d, top) and CSFE-labeled NDMPs (Figure 5c,d, bottom) were co-incubated non-trypan blue-labeled (Figure 5c) and trypan-blue labeled (Figure 5d) peritoneal myeloid cells from naive mice for 1 hour. Treatment with CSFE-labeled NDMPs of quenched, trypan blue-labeled myeloid cells demonstrates persistent CSFE uptake, indicating NDMP endocytosis (46). Taken together, these data demonstrate that the majority of NDMPs express PS, which likely serves as an uptake signal to surrounding phagocytes, specifically F4/80 macrophages.…”
Section: Resultsmentioning
confidence: 99%
“…A strong increase in uptake efficiency, to 16%, was also observed for N7 whereas no significant influence of the lipofectamine coating was seen for mouse astrocytes and SH-SY5Y. We conclude that surface coating and increased incubation time or a combination thereof are suitable methods to achieve high tagging efficiencies in a variety of cell types, even though the intracellular recognition and processing of the resonators by the cells may differ between the two approaches21242526. (We did not find any indication that the different approaches for laser internalization affect the spectral properties of the lasers.…”
Section: Resultsmentioning
confidence: 75%
“…In the literature, different liposome coatings have been reported to assist with the uptake of much smaller polymer microspheres (about 2 μm in size) by non-phagocytic cells212324. Liposomes consist of a formulation of neutral and positively charged lipid molecules that can facilitate contact and fusion with negatively charged cell membranes.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that MCF-10A cells can internalize both positively and negatively charged particles, whereas in SKBR-3 cells the uptake of negative charged particles is low [39,40]. The differences in cell uptake can be explained because Na-ZnTCPP-1·GNP are negatively charged.…”
Section: Photodynamic Effect Of Na-zntcpp-1·gnp On Cell Culturesmentioning
confidence: 94%